American Vanguard: The United Auto Workers During the Reuther Years - Goutor, David (Labour / Le Travail, 2007)
The article reviews the book, "American Vanguard: The United Auto Workers During the Reuther Years," by John Barnard.
Keywords: AMERICAN Vanguard: The United Auto Workers During the Reuther Years (Book); BARNARD; John; BOOKS – Reviews; INTERNATIONAL Union; United Automobile; Aerospace & Agricultural Implement Workers of America; Nonfiction